Pengaruh Kecerdasan Intrapersonal Terhadap Kemampuan Penalaran Matematika Siswa - Badriyah, Badriyah; Pratiwi, Ria Yoni (Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
The purpose of this study is to find out that intrapersonal intelligence has a positive influence on students' mathematical reasoning abilities in the 258 Jakarta Middle School. In addition, the author tries to prove Gardner's opinion that intrapersonal intelligence is not a superior need compared to other intelligences. Survey research method with data analysis techniques using random sampling techniques. The number of samples used was 72 students. In the normality test using Chi-square test, some conclusions can be drawn as follows: The results of the study show that the results of significant regression testing with F test obtained F count = 2.47 by taking a significance level of a = 5% and F table = 2.0 so that F count> It can be concluded that there is a significant effect of intrapersonal intelligence on students 'mathematical reasoning abilities and the contribution of intrapersonal intelligence to students' mathematical reasoning abilities of 8.032%.